The Management Of The Border Region In Perspective International Law (Indonesia-Malaysia) - Maswandi Maswandi (International Asia Of Law and Money Laundering (IAML), 2022)
Mastery of ownership of a region is one of the goals of a country. Problems related to the border between Indonesia and Malaysia often occurs since the independence of each country. Persengketaaan the border region generally arise because of differences in views about the boundary line between one Country over the boundary line which is located in the image. International law has long since set up with a clear and provide legal certainty about the border region of a country. The determination of the boundaries of a country is determined by the processes of international law, both use the concept of self-determination, the principle of uti possidetis, and the boundaries of the state. So the determination of the boundaries of a country are expected to no longer pose a conflict. A bilateral agreement between the Uk and the Netherlands in the period before the independence of Indonesia and Malaysia, has been providing legal certainty about the boundaries between the two countries. So, the legal basis of the colonial government such should be used as reference material for Indonesia and Malaysia to determine the area of each region. Cooperation with the management of the border region between Indonesia and Malaysia need to be improved. This is of course a view that the region border on the Island of Borneo to truly experience inequality, better facilities and infrastructure between the two countries.Quality improvement resources to local communities through capacity building programe, is expected to enhance the role of law enforcement that is based on the local wisdom of the community of the border region.